Marx and art - Alizadeh, Ali (Insolubilia: new work in contemporary philosophy, 2019)
This book advances and enriches the debates and discussions about the value of art. It offers a close reading of passages from Marx's entire body of work and an engaging and accessible narrative of the beginnings, development and discoveries of Marx's thoughts on art.